Understanding the action of bamocaftor as a potential drug candidate against Cystic Fibrosis Transmembrane Regulator protein: A computational approach. - Naisarg Patel; Samrat Sarkar; Bala Murali V M; Ishan Kashyap; Premkumar Thiruselvam; Vino Sundararajan; Sajitha Lulu Sudhakaran (PLoS ONE, 2025)
Cystic Fibrosis (CF) is a hereditary condition and can cause permanent respiration problems leading to degraded life quality. The most common variation leading to CF is the F508del variation. CF can cause damage to not just the lungs but also digestive system, pancreas, and other organs. CF decreases the life expectancy of the individuals affected with the constant fear of lung complications. The current methods of treatment include using a combination of drugs to manage the symptoms. The combination of drugs has many side effects and causes damage to other organs like liver, heart or kidneys. In this study, we aim to find a drug that can relieve the symptoms of CF. We began by creating a dataset of potential drug molecules, which was subsequently refined by removing harmful compounds through an ADMET scan. All these compounds were then docked to the mutated Cystic Fibrosis Transmembrane Regulator (CFTR) protein. The compounds with the best docking affinity were Galicaftor and Bamocaftor. A currently approved drug, Ivacaftor was selected as control for the 200 ns Molecular Dynamics (MD) Simulation. The simulation revealed that the CFTR protein remained more stable and compact when complexed with Bamocaftor, when compared to Ivacaftor and Galicaftor. Moreover, the MMPBSA free energy calculations revealed that the free energy of the CFTR-bamocaftor complex is the lowest compared to the other complexes. Our findings reveal the action of bamocaftor on CFTR protein with p.Phe508del variation. However, the absence of in-vivo or in-vitro studies is a limitation, and further experimental validation is necessary to confirm its efficacy and safety.